Analisis Faktor-Faktor yang Mempengaruhi Jumlah Penduduk Miskin di Provinsi Jawa Timur Tahun 2011-2018 dalam Tinjauan Ekonomi Islam - Arif Luqman Hakim (Falah: Jurnal Ekonomi Syariah, 2019)
East Java is one of the potential provinces on the island of Java consisting of 29 districts and 9 cities. East Java is also a densely populated island, but as the population grows, so does the standard of living that must be fulfilled by the government. If this cannot be fulfilled, poverty will occur. So we need the other factors that can reduce the rate of poverty. The aims of this study is to determine the effect of the Human Development Index (HDI), Growt Rate Domestic Product (GDRP), and unemployment rates on the rate of poverty in the province of East Java in 2011 to 2018. The estimation results of the Data Panel model using Eviews 9 and Microsoft Excel 2007 software. It is known that the HDI, GRDP, and unemployment rates in 2011 to 2018 were able to reduce the number of poor people that occurred in the province of East Java. Besides variable of GRDP, variable of HDI in this study also played a major role in reducing the number of poor people. So in this case the role of the government is needed to improve the HDI in order to reduce the number of poor people in the province of East Java. Because HDI is one factor that in line with Islamic efforts in alleviating poverty.